2011
DOI: 10.1097/bpo.0b013e31820321ab
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Length-Stable Femoral Shaft Fractures in Heavier Children

Abstract: In our weight-matched comparison, the use of TEN resulted in decreased time in operating room, estimated blood loss, and implant-related problems. Malunion and leg length discrepancy remain of concern when heavier patients are treated by TEN, but were not significantly increased relative to RNL in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…There were 37 (62%) Type A fractures, 18 (30%) Type B, and 5 (8%) Type C. Fracture instability was defined as length unstable if it was complex or spiral (the length of the fracture was twice as long as the diameter of the femur at the level of the fracture) [11,40]. Forty (67%) were length-unstable fractures.…”
Section: Methodsmentioning
confidence: 99%
“…There were 37 (62%) Type A fractures, 18 (30%) Type B, and 5 (8%) Type C. Fracture instability was defined as length unstable if it was complex or spiral (the length of the fracture was twice as long as the diameter of the femur at the level of the fracture) [11,40]. Forty (67%) were length-unstable fractures.…”
Section: Methodsmentioning
confidence: 99%
“…7-10 However, recent studies showed an increased risk of complications when flexible nails are used in heavier children and those with fractures of unstable length. [10][11][12][13] Femoral shaft fractures treated with rigid antegrade intramedullary nailing have shown promising results, but this treatment is generally reserved for older children and adolescents. [14][15][16] This technique affords stable internal fixation and allows for early mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Forty percent of patients treated with flexible nails (6/15) experienced complications. 23 Interestingly, the rate of complications in the matched group which underwent rigid locked nailing was not significantly different with 10 of 15 patients having a complication.…”
Section: Discussionmentioning
confidence: 90%